2016
DOI: 10.1149/2.0941614jes
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Transport at the Acid-Alkaline Interface of Bipolar Membranes

Abstract: The combination of cation exchange membrane (CEM) and anion exchange membrane (AEM) electrolytes to form of a hybrid, or bipolar membrane (BPM) electrolyte, can have unique advantages for electrochemical systems including fuel cells, electrolyzers, electrodialysis, and photovoltaic solar-to-fuel devices. However, a major challenge for this approach is the development of a stable and active interfacial region (i.e., junction) that adjoins the CEM and AEM layers. Moreover, a fundamental understanding of transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 52 publications
(98 reference statements)
2
87
0
Order By: Relevance
“…Two possible reasons have been considered for this device failure: the most likely explanation is the enormously large width (∼2 μm) of the neutral region relative to the desired junction, which is 3 orders of magnitude narrower (per the computational supplement to this work done in Ref. 6), resulting in excessive resistance over the interfacial region. Another possible reason is thermal stressing of Nafion due to repeated application of one face to a dry, heated surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two possible reasons have been considered for this device failure: the most likely explanation is the enormously large width (∼2 μm) of the neutral region relative to the desired junction, which is 3 orders of magnitude narrower (per the computational supplement to this work done in Ref. 6), resulting in excessive resistance over the interfacial region. Another possible reason is thermal stressing of Nafion due to repeated application of one face to a dry, heated surface.…”
Section: Resultsmentioning
confidence: 99%
“…A recent publication by Grew 6 provides a computational guideline for transport at the critical PEM/AEM junction in BPM-based devices. In this work, it is shown that for a device with acidic anode and alkaline cathode (Figure 1b), the recombination rate of the proton/hydroxyl groups at the interface is the limiting component for device performance.…”
mentioning
confidence: 99%
“…Assuming E oc is dictated solely by the potential drop across the space-charge region, the value of V oc is less than the magnitude of E oc , 12 and therefore, a larger magnitude E oc also translated to larger V oc values. The decrease in the magnitude of the photocurrent for PSBM could be due to formation of a well-defined and stable space-charge region that is expected to be on the order of several nanometers thick, 32,33 beyond which cPFSA is strongly acidic. Most photogenerated carriers in the space-charge region will charge separate and be collected if the drift length is larger than the width of the space-charge region.…”
Section: Photovoltaic Action Requires Light Absorption By Dyesmentioning
confidence: 99%
“…Reported current densities were calculated by dividing the external current passed through the potentiostat by the geometric area of the membrane exposed to the aqueous electrolyte solution (1.86 cm 2 ). To follow the J-E convention used in our previous publication 20 and prior literature reports of J-E behavior of bipolar membranes where the working electrode is on the acidic side of the bipolar membrane, and therefore P1 is the working electrode in Figure 7, 33,[46][47][48] current and voltage data that were measured with P2 as the working electrode were multiplied by À1. This correction was applied to the data reported in Figures 5, S6, and S7, and the data from mem2S0 and mem7S1 in Table S1.…”
Section: Electrochemical Experimentsmentioning
confidence: 99%
“…Whereas the graphene BPM interface has been proven to enhance WD significantly and offers the potential to provide conductive properties, the spin‐coat deposition method does not lead to high‐level molecular organization in these films, and the interfaces between the materials is not uniform or well defined. It was reported that the structure of the interface, including molecular orientation and roughness, impacts WD in terms of forming efficient pathways for water and ions, distributing the active catalytic sites, and maximizing the electric‐field intensity . For these same reasons, the interface thickness is also very important and also cannot be controlled on the molecular scale by using spin coating.…”
Section: Introductionmentioning
confidence: 99%